Ion-Exchange Resins as Controlled Drug Delivery Carriers - Srikanth, M. V.; Sunil, S. A.; Rao, N. S.; Uhumwangho, M. U.; Ramana Murthy, K. V. (Journal of Scientific Research, 2010)
Ion exchange resins (IER) are insoluble polymers that contain acidic or basic functional groups and have the ability to exchange counter-ions within aqueous solutions surrounding them. Based on the nature of the exchangeable ion of the resin as a cation or anion, it is classified as cationic or anionic exchange resins, respectively. The efficacy of ion exchange resins mainly depends upon their physical properties such as degree of cross-linking, porosity, acid base strength, stability, purity and particle size. Modified release of drugs from resinate (drug-resin complexes) is another potential application of ion exchange resins. Due to the versatile utility of ion exchange resins, they are being used for various drug delivery and therapeutic applications. Resins used are polymers that contain appropriately substituted acidic groups, such as carboxylic and sulfonic for cation exchangers; or basic groups, such as quaternary ammonium group for anion exchangers. This review addresses different types of ion exchange resin, their properties, the chemistry; role of IER in controlled drug delivery systems, its therapeutic applications, methods of preparation of IER along with their resonates. Keywords: Anion exchange; Cation exchange; Resin; Controlled release; Resinates; Drug delivery. © 2010 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v2i3.4991 J. Sci. Res. 2 (3), 599-613 (2010)